Comparison of Military Recruit and Incumbent Physical Characteristics and Performance: Potential Implications for Through-Career Individual Readiness and Occupational Performance. Issue 9 (30th September 2022) - Drain, Jace R.; Debenedictis, Thomas; Bulmer, Sean; Michael, Scott
Abstract: Drain, JR, Debenedictis, T, Bulmer, S, and Michael, S. comparison of military recruit and incumbent physical characteristics and performance: Potential implications for through-career individual readiness and occupational performance. J Strength Cond Res 36(9): 2536–2543, 2022—After basic military training, physical training practices among incumbent personnel differ substantially, potentially precipitating varied physical capacity and operational readiness. The purpose of this retrospective investigation was to compare physical characteristics and physical performance between recruits and incumbent personnel. Data were collected for 222 army recruits (REC: 197 men/25 women) nearing completion of basic training and 280 incumbent army personnel from combat arms (CA: 142 men) and noncombat arms trades (NCA: 113 men/25 women). Height, mass, and body mass index (BMI) were recorded together with performance measures including predicted V̇o 2 max and 1 repetition maximum box lift. Compared with REC, male incumbents were older (21.8 ± 0.6 vs. 27.6 ± 1.2 years; mean ± 95% confidence interval), had greater body mass (77.6 ± 1.3 vs. 82.6 ± 1.5 kg) and BMI (24.2 ± 0.3 vs. 25.8 ± 0.5 kg·m −2 ), similar relative V̇o 2 max, and lower box lift (49.7 ± 1.4 vs. 47.2 ± 2.4 kg). Male CA demonstrated greatest physical performance while male NCA demonstrated the highest BMI and poorest physical performance. Compared with REC, female incumbents were older (22.8 ± 1.6 vs. 31.9 ± 4.4 years), had similar body mass, higher BMI (24.1 ± 0.7 vs. 26.1 ± 2.4 kg·m −2 ), as well as lower V̇o 2 max (42.0 ± 1.3 vs. 37.9 ± 2.1 ml·kg· −1 ·min −1 ) and box lift (27.8 ± 2.1 vs. 23.3 ± 2.4 kg). More than 97% of men and approximately 75% of women were able to achieve the box lift and V̇o 2 max baseline standards. The older age category (26 + vs. 18–25 years) typically demonstrated higher BMI and lower physical performance. Through-career maintenance of physical capacity is important for military personnel to support individual readiness and occupational performance, preserve health, and mitigate musculoskeletal injury risk.